The influence of external factors on corporate strategy and strategies for adaptation in light of the global challenges (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2024)
This study investigates the influence of external factors on corporate strategy and explores strategies for adaptation in the face of global challenges. The primary objective is to analyze how various external variables including economic conditions, technological advancements, regulatory shifts, and socio-cultural changes affect corporate decision-making and strategic planning. Utilizing a quantitative research methodology, the study involved a structured survey distributed to a sample of 116 corporate executives across diverse industries, allowing for a comprehensive analysis of the data collected. Statistical techniques were employed to identify correlations between the external factors and the strategic adaptations implemented by organizations. The findings reveal that economic fluctuations and rapid technological innovations are the most significant external influences on corporate strategies. Companies that proactively respond to these changes tend to exhibit greater resilience, enhanced market competitiveness, and improved long-term sustainability. The research underscores that organizations that incorporate external insights into their strategic planning are more capable of developing effective responses to evolving challenges. To address these findings, the study offers several recommendations: organizations should enhance their agility by investing in thorough market research and establishing flexible strategic frameworks that can swiftly adapt to external changes. Furthermore, fostering a culture of innovation and continuous learning within the organization is crucial for navigating the complexities of global challenges effectively. By embracing these adaptive strategies, companies not only prepare themselves to confront immediate challenges but also position themselves favorably for future opportunities in a rapidly changing environment. Ultimately, this research contributes valuable insights to the literature on corporate strategy, emphasizing the necessity of understanding external dynamics and implementing adaptive strategies for organizational success in today’s competitive landscape. The study provides a foundation for further exploration into how organizations can strategically navigate external influences while maintaining agility and responsiveness in their operations.